2018
DOI: 10.1007/s12035-018-0909-z
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Protein Biomarkers and Neuroproteomics Characterization of Microvesicles/Exosomes from Human Cerebrospinal Fluid Following Traumatic Brain Injury

Abstract: The original version of this article unfortunately contained a typographical error on Author's name BFiras Kobessiy^. This should be corrected as BFiras Kobeissy^.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Upregulation of molecular chaperones rescues the NF phenotype in SACS knockout neurons (Engert et al, 2000) and in motor neurons expressing mutant NfL associated with CMT (Tradewell et al, 2009). Chaperones have the potential to increase a more mobile pool of NF proteins accessible to secretory mechanisms such MVB (Manek et al, 2018).…”
Section: Release and Clearance Of Nf Peptides And Proteinsmentioning
confidence: 99%
“…Upregulation of molecular chaperones rescues the NF phenotype in SACS knockout neurons (Engert et al, 2000) and in motor neurons expressing mutant NfL associated with CMT (Tradewell et al, 2009). Chaperones have the potential to increase a more mobile pool of NF proteins accessible to secretory mechanisms such MVB (Manek et al, 2018).…”
Section: Release and Clearance Of Nf Peptides And Proteinsmentioning
confidence: 99%
“…These molecules move to their destination in EVs, which are small vesicles coated with a phospholipid bilayer and a cargo of bioactive molecules that represents the contents of the cell in which the vesicle originated [194][195][196]. EVs are released into the extracellular space by all cell types and, consequently, are ubiquitously present in biological fluids, for example, blood [197], urine [198], saliva [199], cerebrospinal fluid [200], and breast milk [201]. EV biogenesis represents an important evolutionary advancement because the cargo is protected from degradation by ribonucleases, deoxyribonucleases, and proteases present in the extracellular space.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…In recent years, the changes in the exosomal content during the development of disease in patients with TBI have been extensively studied. Brain-injury biomarkers were detected in the CSF exosomes of patients with TBI, such as αII-spectrin breakdown products (BDPs), glial fibrillary acidic protein and its BDPs, ubiquitin C-terminal hydrolase-L1, synaptophysin, and Alix (Manek et al, 2018 ). This study found that after the occurrence of TBI, changes in the levels of exosomes and their markers in the plasma or CSF does not just diagnose TBI but also stages patients with TBI (Beard et al, 2020 ; Peltz et al, 2020 ).…”
Section: Exosomes and Traumatic Brain Injurymentioning
confidence: 99%